2018
DOI: 10.17728/jatp.2224
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Antosianin dan Aktivitas Antioksidan Tepung Uwi Ungu selama Penyimpanan

Abstract: Uwi ungu (Dioscorea alata L) merupakan bahan pangan yang berpotensi sebagai sumber antioksidan alami, karena adanya komponen antosianin dan senyawa fenolik. Penelitian ini bertujuan mengetahui perubahan komponen tepung uwi ungu selama penyimpanan pada kondisi ruang simpan berbeda. Penyimpanan tepung uwi ungu disimpan pada ruang berukuran 60x60x60 cm 3 yang diberi perlakuan lampu 150 lux (ruang KL) dan tanpa perlakuan lampu (TKL). Kelembaban udara (RH) ruang simpan dicatat pada saat penyimpanan. Penyimpanan dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…The statistical test results of anthocyanin levels showed that the baking temperature had no effect on anthocyanin levels ( p > 0.05), while the treatment of adding the purple yam flour had an effect on the anthocyanin levels of the fresh bread ( p < 0.05). A study of Tamaroh et al [ 10 ] showed that the anthocyanin level in the purple yam flour is 82.72 mg/100 g db. Another latest study by Ratnaningsih et al [ 15 ] showed that the anthocyanin content in purple yam flour is 74.3 mg/100 g. The anthocyanin value of the eight plain bread formulated with purple yam flour increased ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The statistical test results of anthocyanin levels showed that the baking temperature had no effect on anthocyanin levels ( p > 0.05), while the treatment of adding the purple yam flour had an effect on the anthocyanin levels of the fresh bread ( p < 0.05). A study of Tamaroh et al [ 10 ] showed that the anthocyanin level in the purple yam flour is 82.72 mg/100 g db. Another latest study by Ratnaningsih et al [ 15 ] showed that the anthocyanin content in purple yam flour is 74.3 mg/100 g. The anthocyanin value of the eight plain bread formulated with purple yam flour increased ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The total phenol content of plain bread further increased with the addition of yam flour. Studies of [ 10 ] showed the total phenol content in purple yam flour (454.67 mg GAE/100 g db). In a previous study, Hong and Koh [ 21 ] stated that the baking processing method has no effect on the total phenolic content of purple sweet potato.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations